Effect of age-by-carcass weight classification on carcass traits, cutability and fat-partitioning of Barbari male goats - Pal, U K; Agnihotri, M K (The Indian Journal of Animal Sciences, 2012)
The influence of carcass weight classification within kid (6 months to 1 year), yearling (1 to 2 years) and mature (> 2 years) categories on carcass traits, its cutability and fat-partitioning was studied using Barbari male goat (60) carcasses. Heavier carcass weight classes within each age category having higher(P